The zero night [large type] - Freeman, Brian, 1963- (Freeman, Brian, 1963- Jonathan Stride novel., 2022)
Attorney Gavin Webster says he paid $100,000 in ransom to the men who kidnapped his wife. Now they've disappeared with the cash. But Jonathan Stride learns the lawyer had plenty of motive to mastermind the crime. And as Stride digs for the truth about Gavin Webster and his wife, he must also deal with a crisis in his own marriage.